Fighting on Both Fronts: The Struggle for Women's Liberation in Conjunction with the Sandinista Rebellion - Morazan, Johanna (The Toro Historical Review, 2022)
The Nicaraguan revolution not only launched complete legislative and gubernatoral changes within the country in 1979, but the people's revolution also launched a movement among women civilain populations that would engage in the rebellion against the Somoza dictatorship and later counterrevolutionatries. The emphasis of the women's involvement lies within the implemenation of feminist ideology within the Sandinista socialist party by its most prominent figures and the Sandisinta party's subsequent facilitatation of new women's organizations. The emegence of women as activists and leaders served two concurrent purposes: to secure the freedom of the nation from the Somoza regime and the emancipation of women. This article examines the role of women throughout the course of the goverment overthrow and the correlation between the Sandinista movement and the women's liberation movement in Nicaragua.